Plant-Wide Target Metabolomics Provides a Novel Interpretation of the Changes in Chemical Components during Dendrobium officinale Traditional Processing - Pengfei Liu; Bei Fan; Yuwen Mu; Litao Tong; Cong Lu; Long Li; Jiameng Liu; Jing Sun; Fengzhong Wang (MDPI AG, 2023)
The traditional processing of Dendrobium officinale (DO) is performed in five necessary processing steps: processing fresh strips, drying at 85 °C, curling, molding, and drying at 35 °C (Fengdou). The antioxidant activity of DO is increased after it is processed into Fengdou. To comprehensively analyze the changes in the functional components, a plant-wide target metabolomics approach was employed. In total, 739 differential chemical components were identified in five processing treatments, mainly highlighting differences in the levels of phenolic acids, flavonoids, lipids, and amino acids and their derivatives, and the glycosylation of aglycone resulted in the upregulation of flavonoid glycoside levels. Temperature is a key factor in DO processing during production. In addition, the enrichment of specific differential chemical components was found mainly in five different metabolic pathways: glucosinolate biosynthesis, linoleic acid metabolism, flavonoid biosynthesis, phenylpropanoid biosynthesis, and ubiquinone and other terpene quinone biosynthesis. A correlation analysis clarified that total phenols and flavonoids show a significant positive correlation with antioxidant capacity. This study provides new insights into the influence of the processing processes on DO quality, which may provide guidance for the high-quality production of DO.